A Wearable Research System for Combined Cochleo-Vestibular Stimulation - David Lanthaler; Patrick P. Huebner; Matthew D. Parker; Andreas Griessner; Viktor Steixner; Clemens M. Zierhofer (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Cochlear implants (CI) are a well-established treatment option for patients with severe to profound hearing loss, while vestibular implant (VI) trials give a promising outlook for patients with severely impaired vestibular function. In a number of subjects these two conditions may also present together, necessitating treatment with a cochleo-vestibular implant (CVI). While the feasibility of CVIs has been demonstrated, no wearable processor has existed to provide target-specific, modulated stimulation for both systems over extended periods. We introduce a first wearable audio-motion processor (AMP) system designed to be used in conjunction with a CVI. We first present the architecture of the AMP, along with the possible modes of operation. We then use a testbench to show the functionality and limits of the presented device. Important performance characteristics of such a system are the latency between head movements and resulting vestibular stimulation pulses, and the deviations of stimulation amplitudes and pulse rates from a programmed transfer function (TF). The device was tested using amplitude- and rate-modulated vestibular pulses in response to predefined single-axis rotations performed on a rotary platform, while providing simultaneous auditory stimulation to cochlear electrodes. We were able to achieve a recorded latency comparable to the physiological response time of normal vestibular organs. The results for the TF showed that the measured values for the pulse rates and the amplitudes followed the reference values very accurately. This audio-motion processor is the world’s first wearable processor capable of delivering combined, specifically modulated cochlear and vestibular stimulation.